PENGUATAN KETERAMPILAN KEWARGANEGARAAN MELALUI KETERLIBATAN DALAM MENUNJANG PENALARAN MORAL MAHASISWA (STUDI PADA HIMPUNAN MAHASISWA PKNH UNY) - Yayuk Hidayah, Annisa Istiqomah; Roul Alvaro Prasetyo3; Iqbal Arpannudin (LPPM Universitas Cipta Mandiri, 2024)
This research aims to find out how to strengthen citizenship skills through involvement in supporting students' moral reasoning in the UNY PKnH student association. Qualitative research with a descriptive approach, data collection through structured interviews, observation and documentation with a total of 10 administrators and members as informants for the 2022-2023 period. Data validation uses triangulation. The results of the research show that the citizenship skills of students in the PKnH UNY student association cover 3 (three) domains, namely attitudes, knowledge and skills. Involvement for students involved in the PKnH UNY student association is that they feel that their activities are meaningful and can influence the situation and course of work programs in the PKnH UNY student association. The moral reasoning of students in the PKnH UNY student association is to consider, assess and decide based on moral principles of good and bad, ethical and unethical in running the organization. The actualization of Pancasila values for students in the UNY PKnH Student Association is the dominant driving element in the UNY PKnH student association. Student motivation in joining the UNY PKnH Student Association comes from internal and external sources. Internal factors include 1) self-desires, 2) the need to socialize. Meanwhile, external factors include 1) the campus academic environment, 2) characterization in the UNY PKnH Student Association. Further research on moral reasoning is recommended in this study